2003
DOI: 10.1037/0021-9010.88.3.518
|View full text |Cite
|
Sign up to set email alerts
|

Recovery, work engagement, and proactive behavior: A new look at the interface between nonwork and work.

Abstract: This study examined work-related outcomes of recovery during leisure time. A total of 147 employees completed a questionnaire and a daily survey over a period of 5 consecutive work days. Multilevel analyses showed that day-level recovery was positively related to day-level work engagement and day-level proactive behavior (personal initiative, pursuit of learning) during the subsequent work day. The data suggest considerable daily fluctuations in behavior and attitudes at work, with evidence that these are rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

69
1,187
6
86

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,423 publications
(1,348 citation statements)
references
References 61 publications
69
1,187
6
86
Order By: Relevance
“…In line with previous research (Fritz et al, 2010;Sonnentag, 2003), we controlled for work demands that were negatively related to psychological detachment. Intercepts indicate the mean sleep quality and psychological detachment level on a Monday.…”
Section: Mindfulness and Change Trajectories In Psychological Detachmmentioning
confidence: 93%
See 2 more Smart Citations
“…In line with previous research (Fritz et al, 2010;Sonnentag, 2003), we controlled for work demands that were negatively related to psychological detachment. Intercepts indicate the mean sleep quality and psychological detachment level on a Monday.…”
Section: Mindfulness and Change Trajectories In Psychological Detachmmentioning
confidence: 93%
“…Recovery research has revealed that work characteristics like workload or time pressure have an effect on an individual's sense of well-being before going to sleep and on other recovery-related variables (Sonnentag, 2001;Sonnentag & Zijlstra, 2006). Researchers have therefore frequently controlled for work characteristics when investigating recoveryrelated variables like psychological detachment (e.g., Fritz et al, 2010;Sonnentag, 2003). In order to be able to control for potential confounding effects, we therefore chose to control for workload and time pressure with a German translation of the Questionnaire on the Experience and Evaluation of Work (VBBA; van Veldhoven & Meijman, 1994; see also Bakker, Veldhoven, & Xanthooulou, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies have also started to investigate momentary episodes of work engagement (Sonnentag, 2003) and performance (Beal, Weiss, Barros, & MacDermid, 2005), and concluded that meaningful variations exist not only at the between-person, but also at the within-person level. Therefore, the purpose of the present study is to test, for the first time, how variations in job resources may determine state levels of work engagement, through the enhancement of employees' state self-efficacy beliefs over time.…”
Section: The Present Studymentioning
confidence: 99%
“…Empirical research has shown that insufficient recovery is associated with poor psychological and physical health, such as psychosomatic complaints and burnout (Elfering, Grebner, Semmer, & Gerber, 2002;Sluiter, Van der Beek, & Frings-Dresen, 1999). Moreover, research evidence suggests that individuals' well-being and work behavior benefit from respite time during evening hours (Sonnentag, 2001(Sonnentag, , 2003 as well as from longer respite periods such as vacations (Westman & Eden, 1997;Westman & Etzion, 2001). It seems, however, that it is not merely the amount of the time available for respite and recovery that matters; the quality of the respite experience also plays an important role in the recovery process (Etzion, Eden, & Lapidot, 1998;Lounsbury & Hoopes, 1986;Westman & Eden, 1997).…”
mentioning
confidence: 99%